ĐA DẠNG ĐỘNG VẬT ĐÁY Ở SÔNG CHANH, TỈNH QUẢNG NINH - Nguyễn, Tống Cường; Lê, Hùng Anh; Trần, Đức Lương (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
MACROBENTHOS DIVERSITY IN CHANH RIVER, QUANG NINH PROVINCEThe macrobenthos fauna in the Chanh River, Quang Ninh province have been studied for two surveyed, from September 2020 to May 2021. A total of 99 macrobenthos species belonging to three phyla, five class, 19 orders, 37 families and 58 genera were collected and identified. The most dominant phyla of macrobenthos were Mollusca (55 species) followed by Arthropoda (40 species) and Annelida (4 species). Two vulnerable (Tachypleus tridentatus, Charybdis feriata) macrobenthos species of Vietnam Red Data Book (2007) were recorded and one endangered (Tachypleus tridentatus) species was also listed in IUCN Red List (2021).